How to take an ant's pulse: a procedure for non‐destructively monitoring baseline and stimulated heart rate in Formicidae. Issue 9 (14th June 2021) - Davis, Andrew K.; Clancy, Kathleen Mei; Sasaki, Takao
Abstract: Ants, like other insects, have a heart that pumps hemolymph rhythmically. We designed an apparatus and procedure to non‐destructively monitor the rate of cardiac contractions in ants, using a modified light microscope and infrared light. This allowed us to obtain the first baseline heart rate data on three ant species, collected in Georgia, USA. We next describe how ant heart rates can be stimulated, for comparing cardiac reactions among colonies, or for assessing stress responses. The procedures described here may be useful for other researchers interested in ant physiology. Abstract : Ants, like other insects, have a heart that pumps hemolymph rhythmically. We designed an apparatus and procedure to non‐destructively monitor the rate of cardiac contractions in ants, using a modified light microscope and infrared light. This allowed us to obtain the first baseline heart rate data on three ant species, collected in Georgia, USA. We next describe how ant heart rates can be stimulated, for comparing cardiac reactions among colonies, or for assessing stress responses. The procedures described here may be useful for other researchers interested in ant physiology.